2013
DOI: 10.29379/jedem.v5i1.206
|View full text |Cite
|
Sign up to set email alerts
|

A Trigger or a Muffler? - Examining the Dynamics of Crosscutting Exposure and Political Expression in Online Social Media

Abstract: This study explores the potential of online social media to serve as a sphere for political discourse and investigates the extent to which everyday uses of online social networking sites can expose citizens to politically diverse viewpoints.  In addition, this study asks whether such crosscutting exposure in online social networks will act as a trigger or a muffler for political expression – that is, whether exposure political difference will stimulate or discourage political discussions.  With analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our results, showing that people receiving belief-congruent information are more willing to politically participate than people receiving incongruent information, are in line with other experimental research on the relationship between crosscutting exposure and political participation [4,18,19]. When looking at the entire literature, however, this relationship becomes less clear since past studies found both negative and positive as well as no relationships between cross-cutting exposure and political participation [e.g., 3,10,12,21]. A meta-analysis also found no overall effect [5].…”
Section: Effects Of Attitudinal Congruence On Political Participation...supporting
confidence: 89%
See 1 more Smart Citation
“…Our results, showing that people receiving belief-congruent information are more willing to politically participate than people receiving incongruent information, are in line with other experimental research on the relationship between crosscutting exposure and political participation [4,18,19]. When looking at the entire literature, however, this relationship becomes less clear since past studies found both negative and positive as well as no relationships between cross-cutting exposure and political participation [e.g., 3,10,12,21]. A meta-analysis also found no overall effect [5].…”
Section: Effects Of Attitudinal Congruence On Political Participation...supporting
confidence: 89%
“…Instead, it assumes that the confrontation with opposing opinions could actually increase political participation by fostering political learning and increased polarization [5]. This reasoning is supported by studies that find a positive relationship between cross-cutting exposure and political participation [12,[21][22][23].…”
Section: Effects Of Attitudinal Congruence On Political Participationmentioning
confidence: 98%
“…It may be that some online platforms have become popular conduits for critics of the government and government policies to voice their opinions. This is supported by studies that show that anonymous communication leads to more uninhibited acts and is more relevant than when the speaker is identified in face-to-face conditions (Bae, 2013;Lee et al, 2018). However, another study has also found that controversial newsgroups or online forums with high levels of negative emotions may not necessarily be classified as communities, as they may lack a shared goal and identity (Nguyen et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Our results, showing that people receiving belief-congruent information are more willing to politically participate than people receiving incongruent information, are in line with other experimental research on the relationship between cross-cutting exposure and political participation ( Moehler and Conroy-Krutz, 2016 ; Shi, 2016 ; Wojcieszak et al, 2016 ). When looking at the entire literature, however, this relationship becomes less clear since past studies found both negative and positive as well as no relationships between cross-cutting exposure and political participation (e.g., Mutz, 2002 ; Quintelier et al, 2012 ; Bae, 2013 ; Feezell, 2016 ; Matthes et al, 2019 ). One possible reason for these discrepancies could lie in different definitions and operationalizations of cross-cutting exposure ( Klofstad et al, 2013 ) as well as different research methods.…”
Section: Discussionmentioning
confidence: 98%